Comparison of foam glass-ceramics with different composition derived from Ark Clamshell (ACS) and Soda Lime Silica (SLS) glass bottles sintered at various temperatures - Noor Hisham, Noor Aizat; Mohd Zaid, Mohd Hafiz; Ab Aziz, Sidek; Muhammad, Farah Diana (Multidisciplinary Digital Publishing Institute, 2021)
Soda lime silica (SLS) waste as the source of silica (SiO2) and ark clamshell (ACS) as the foaming agent has been utilized to fabricate the low-cost and lightweight foam glass-ceramics. A series of 1 and 6 wt% foam glass-ceramics were successfully prepared by the conventional solid-state sintering method at various sintering temperatures for 60 min. The bulk density of the samples has achieved minimum density (1.014 g/cm3) with maximum expansion (62.31%) at 6 wt% of the ACS content sintered at 800 °C for 60 min. The bulk density increases while the linear shrinkage and total porosity decrease with the progression of ACS contents and sintering temperature, where the results correspond with the FESEM micrograph. The result of XRD and FTIR transmittance spectra have shown that the formation of wollastonite crystal has occurred starting at 6 wt% of the ACS content sintered at 800 °C for 30 min. The highest mechanical performance (3.90 MPa) with an average total porosity (8.04%) is observed for the sample containing 1 wt% of ACS. It can be concluded that the composition of foam glass-ceramics (1 and 6 wt%) and sintering temperatures give significant results to the structural, physical, and mechanical properties of the fabricated foam glass-ceramics.